Desenvolvimento de um modelo de vacinação contra Toxoplasma gondii empregando adenovírus recombinante - Braulia Costa Caetano (2005)
In the present study, genes encoding the SAG1, SAG2 and SAG3 proteins of T. gondii were cloned into replication-deficient recombinant adenoviruses, after being modified for appropriate expression in mammalian cells. Modifications included removal of 3-end sequences encoding the GPI-anchoring motifs and, for SAG3, substitution of the 5´-end encoding the natural signal sequence for the influenza virus haemaglutinin signal sequence (HASS). After the characterization of the three recombinant adenoviruses and demonstration of in vitro expression of the SAG proteins, the viruses were employed in immunizations of BALB/c mice. Vaccination with the three recombinants led to production of specific anti-SAG IgG antibodies and also induced activation of specific IFN- producing CD8+ T cells. To determine if the vaccination with the recombinant vectors is capable of eliciting protection against the parasite, animals received a challenge with the highly virulent RH strain or, alternatively, the cystogenic P-Br strain. Results show that vaccination with SAG-recombinant adenoviruses did not increase the survival of animals after challenge with the RH strain, but promoted a significant decrease of 50-80% in brain cyst numbers in groups that received the P-Br strain. In such way, we conclude that immunization with recombinant adenoviruses encoding the T. gondii SAG1, SAG2 and SAG3 antigens is capable of activate specific Th1-biased immune responses against those proteins, and protect against common infective forms of the parasite.